'I have a lot of faith in her': Value of community health workers in addressing family planning in rural Ghana. Issue 10 (2nd October 2020) - Stephens, Maya J.; Schrumpf, Leah A.; Nsarko, Nathaniel E.; Baumgartner, Joy Noel; Ohemeng-Dapaah, Seth; Akosah, Eric; Watt, Melissa H.
ABSTRACT: In rural settings with shortages in trained health care workers, community health workers (CHWs) play an important role in the delivery of health care services. The Ghana Health Service initiated a national CHW programme in 2016 to expand health services to rural populations. This study explored the perceived role and value of CHWs in addressing family planning issues in the Amansie West district of Ghana. The study included in-depth interviews (IDIs) with 28 women in the community, ages 18–49, and 30 CHWs. Using inductive thematic analysis, IDIs were coded to explore opinions on the CHWs' role and perceived value in the delivery of family planning. Participants explained that CHWs provided family planning as part of a healthcare package through household visits and referrals to government services. The value of CHWs in delivering family planning was seen in confidentiality, accessibility, and comfort. Participants recommended an enlarged CHW workforce with a range of commodities and programmatic support. The findings suggest CHWs play an important role in promoting family planning, by serving as a bridge between the community and clinics. In rural communities where resources are scarce, CHWs are an invaluable part of the broader healthcare system.